Surface Coverage of Vascular Grafts with Cultured Human Endothelial Cells from Subcutaneous Fat Tissue Obtained with a Biopsy Needle - Koyama, Masayuki; Satoh, Kei; Yoshida, Hidemi; Suzuki, Sohei; Koie, Hisaaki; Takamatsu, Shigeru (Thrombosis and Haemostasis, 1996)
Surface coverage with autogeneous endothelial cells is effective in reducing thrombogenicity of an artificial vascular graft, but procedure for obtaining the cells is invasive for patients. The purpose of this study was to establish cultures of human endothelial cells separated from a small piece of subcutaneous fat tissue. A piece of tissue weighing about 10 mg was obtained from subcutaneous fat using a biopsy needle, and treated with collagenase and dispase. Microvascular endothelial cells were selected and other types of cells contaminating the cultures were eliminated by scraping with a needle under a microscope. The yield of the cells was 8362 ± 4264/10 mg of subcutaneous fat (n = 7). The cultures reached confluence in about 2 weeks. The cells were positive for von Willebrand factor, P-selectin, and uptake of acetylated low density lipoprotein. The cells produced 15.9 ± 3.3 ng/mg cell protein/h of 6-ketoprostaglandin F1α (n = 5) when stimulated with thrombin. Thrombin also stimulated the production of platelet-activating factor: 7653 ± 4297 dpm/106 cells (n = 5). Endothelin-1 accumulation in the medium of unstimulated endothelial cells was 0.54 ± 0.16 ng/mg cell protein/10 h (n = 8). As a preliminary experiment for graft seeding, the cells were also cultured on pieces of a gelatin-coated Dacron graft, and scanning electron microscopy revealed the surface coverage of the graft. We herein described about successful culture of human microvascular endothelial cells from subcutaneous fat tissue obtained using a biopsy needle. The cultured cells may be applicable to a seeded vascular graft.